Combining diagnostic procedures for the management of leishmaniasis in areas with high prevalence of Leishmania guyanensis Procedimentos diagnósticos combinados no manejo da leishmaniose em áreas com alta prevalência de Leishmania guyanensis - Ednelza de Almeida Benicio; Ellen Pricilla Nunes Gadelha; Anette Talhari; Roberto Moreira da Silva Jr; Luis Carlos Ferreira; Mayara Cristina Cordeiro dos Santos; Marcelo Távora Mira; Cintia Mara Costa de Oliveira; Carolina Talhari; Sinésio Talhari; Paulo Roberto Machado; Albert Schriefer (Sociedade Brasileira de Dermatologia, 2011)
BACKGROUND: The Amazon region corresponds to approximately 40% of the cases of leishmaniasis in Brazil. We report a prospective study with 180 patients conducted in a health care unit that diagnoses 10% of the cases of leishmaniasis in the Brazilian Amazon. The study addresses how a combination of procedures improves diagnosis in areas with high prevalence of Leishmania guyanensis. OBJECTIVES: to evaluate diagnostic methods in areas with high prevalence of Leishmania guyanensis. METHODS: All subjects were amastigote-positive by direct microscopic examination of lesion scarifications. We conducted skin biopsy and histopathology, polymerase chain reaction and parasite cultivation. RESULTS: Polymerase chain reaction detected almost ninety percent of infections when two amplification protocols were used (mini-exon and HSP-70). HSP-70 specific polymerase chain reaction matched the sensitivity of parasite cultivation plus histopathology. CONCLUSION: The best combination was polymerase chain reaction plus histopathology, which increased diagnostic sensitivity to 94%. Species discrimination by polymerase chain reaction disclosed prevalence of human infections with Leishmania guyanensis of 94% and with Leishmania braziliensis of 6% for this region FUNDAMENTOS: O Amazonas corresponde a aproximadamente 40% dos casos de leishmaniose do país. Nós reportamos um estudo prospectivo com 180 pacientes de uma unidade de saúde que diagnostica 10% dos casos de leishmaniose da amazônia brasileira, com combinação de métodos diagnóstico em área de alta prevalência de Leishmania guyanensis. OBJETIVOS: avaliar métodos diagnóstico da Leishmaniose em área endêmica para Leishmania Amazonensis. MÉTODOS: Todos os pacientes tiveram exame direto positivo com presença de amastigotas. Foi feita também biópsia cutânea, com realização de exame histológico, reação em cadeia da polimerase e cultura. RESULTADO: A reação em cadeia da polimerase detectou aproximadamente 90% de infecção quando foram usados duas técnicas de amplificação (mini-exon and HSP-70). A reação em cadeia da polimerase com HSP-70 foi mais sensível que a cultura associada à histopatologia. CONCLUSÃO: A melhor combinação foi a reação em cadeia da polimerase com histopatologia, com sensibilidade de 94%. A discrimanação das espécies causadoras de infecção humana nessa região mostrou Leishmania guyanensis em 94% dos casos e Leishmania brasiliensis em 6%